Investigating Netspeak Applied in Youth Interaction in X Base Account: Word Formation Analysis - Puspitasari, Intan Marta (Language Horizon: Journal of Language Studies, 2024)
In this modern era, the youth actively engage with social media, and they may use abbreviations, slang, and code-mixing to have online texting. This study examines netspeak used by youth in X base accounts. The type of this study is qualitative. The data was collected from various tweets in the @convomf and @tanyarl X accounts for a month. The result shows 102 data on netspeak coming from various forms based on the word formation perspective. This study revealed that one data may involve more than one word formation process, so it can be analyzed in multiple forms. The most common form was an abbreviation, including an acronym inside because the youth love to type less and minimize the words used while sending messages. It deals with the rules of X that the users can only send messages in 1-40 characters through a tweet. However, using acronyms, such as wta and cmiiw, were typed improperly because they used lowercase. Since they use online texting informally, they do not need to pay attention to the formal grammatical rules. Apart from the most common data found, the least data found is the adjectival compound. In the process of adjectival compound, young people may experience difficulties in combining adjectives as the head with other categories as modifiers to create new meanings.